A simple field test for the assessment of aerobic swimming fitness: A multidimensional approch - Dopsaj, M.; Di Nino, A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
From the viewpoint of kinematics, swimming is a cyclical sport, while in terms of energy system loads, it predominantly belongs to endurance sports (Maglischo 2003). The aerobic energy system is basic for the support of a wide range of endurance effort in sport. Both in training and competition, swimmers will benefit from a well-developed aerobic energy system regardless ofthe type of performance required in sprint, middle distance or long distance swimming (Oibrecht 2000). The training process involves many years of continuous and systematic work, which comprises a time cycle with different training methods and goals at which training regimes are aimed. However, during a given period of the training cycle, the coach must have a method or methods that are objective and easy to apply in order to control the competitive level of important physical abilities of swimmers, including the capacity of the aerobic energy system, i.e. of endurance fitness. lt is well known that blood lactate concentrations are the best indicators of the achieved swimming intensity (Oibrecht 2000). Also, lactate testing has already been used in the process of training optimisation, as increasing the concentration of lactate in the blood is the main metabolic mechanism responsible for the appearance of fatigue in swimmers during the training sessions or in the race. As the process of training is aimed to improve the swimmer's results, that is, to increase the swimming velocity in the race, this implies that the ratio between swimming velocity and the achieved lactate concentrations can provide a basic two dimensional (2D) model useful for the coach in the objective control of the training process and the assessment of actual adaptation levels in swimmers. The aim of this research was to define the generic model for a simple, valid and user-friendly field test for the coach to assess the levels of actual general aerobic fitness independent of the type of the swimmer (sprint, middle or long distance), which would be conducted by using only two variables: the swimming velocity and the lactate concentration levels.